Autoimmune Hepatitis (AIH) in Acquired Immune Deficiency Syndrome (AIDS): A Case Report and Review of Literature - Jordan Roussel; Sudha Pandit; Paul Jordan; Moheb Boktor; Kurt Knowles; Nester Dela Cruz; Hrishikesh Samant (Case Reports in Hepatology)
The common causes of abnormal liver chemistries in human immunodeficiency virus (HIV) infected patients are multifactorial. Diagnosis of autoimmune hepatitis (AIH) in HIV infected patients is intriguing but data is scarce. Unmasking of AIH during immune reconstitution in HIV patients after starting antiretroviral therapy is reported but not with advanced acquired immunodeficiency syndrome (AIDS). Here we present a fascinating case of 32-year-old African-American man with advanced AIDS who presented with elevated transaminases. He was diagnosed with AIH before starting antiretroviral therapy and successfully treated with prednisolone and azathioprine with antiretroviral therapy despite very low CD4 count.